Safety of vaccine adjuvants: Focus on autoimmunity. Issue 13 (24th March 2015) - van der Laan, Jan Willem; Gould, Sarah; Tanir, Jennifer Y.; ,
Highlights: Industrial, academic, and governmental experts studied vaccine adjuvants safety. Evidence of signals for autoimmune disorders associated with adjuvants was reviewed. Existing adjuvants (used in marketed vaccines) and novel adjuvants were included. The focus was on oil-in-water emulsion and toll-like receptor agonist adjuvants. No compelling evidence was found associating adjuvants and autoimmunity in humans. Abstract: Questions have been recently raised regarding the safety of vaccine adjuvants, particularly in relation to autoimmunity or autoimmune disease(s)/disorder(s) (AID). The International Life Sciences Institute (ILSI) Health and Environmental Sciences Institute (HESI) formed a scientific committee and convened a 2-day workshop, consisting of technical experts from around the world representing academia, government regulatory agencies, and industry, to investigate and openly discuss the issues around adjuvant safety in vaccines. The types of adjuvants considered included oil-in-water emulsions and toll-like receptor (TLR) agonists. The state of science around the use of animal models and biomarkers for the evaluation and prediction of AID were also discussed. Following extensive literature reviews by the HESI committee, and presentations by experts at the workshop, several key points were identified, including the value of animal models used to study autoimmunity and AID toward studying novel vaccine adjuvants; whether there is scientific evidence indicating an intrinsic risk of autoimmunity and AID with adjuvants, or a higher risk resulting from the mechanism of action; and if there is compelling clinical data linking adjuvants and AID. The tripartite group of experts concluded that there is no compelling evidence supporting the association of vaccine adjuvants with autoimmunity signals. Additionally, it is recommended that future research on the potential effects of vaccine adjuvants on AID should consider carefully the experimental design in animal models particularly if they are to be used in any risk assessment, as an improper design and model could result in misleading information. Finally, studies on the mechanistic aspects and potential biomarkers related to adjuvants and autoimmunity phenomena could be developed.